Metastatic Leiomyosarcoma in African Goose (Anser cygnoides) - Silva, Raquel Annes Fagundes; Olinda, Robério Gomes; Galiza, Glauco Jose Nogueira de; Dantas, Antonio Flávio Medeiros (Acta Scientiae Veterinariae, 2021)
Background: In birds, neoplasms are more frequently observed in Psittaciformes and Galliformes and rarely seen in Columbiformes and Anseriformes, with few reports of the occurrence of mesenchymal neoplasms such as leiomyosarcoma affecting birds. Therefore, the objective of this study was to describe a case of metastatic leiomyosarcoma in an African goose (Anser cygnoides), analyzing the epidemiological, clinical and pathological aspects. Case: A 10-month-old male African goose, was referred to the Veterinary Hospital, Universidade Federal de Campina Grande, Patos, Paraiba, Brazil, whit ataxia, tremors of intention in the head, and nystagmus about one month ago, progressing to lateral decubitus. Due to the unfavorable prognosis, animal was euthanized. Samples of the organs of the coelomic cavity and central nervous system were collected for histologic examination. The samples were fixed in 10% buffered formalin. After fixation, the organs were embedded in paraffin, cut into 4-5 μm sections, and then stained with hematoxylin and eosin. Paraffin blocks with liver, kidney and encephalon fragments were selected and sent for immunohistochemical analysis. The primary antibodies used were: alpha-smooth muscle actin (monoclonal 1A4), anti-vimentin (monoclonal, V9), CD57 (monoclonal, NK1) and cytokeratin (monoclonal, AE1/AE3) and incubated for 18 h at 4Cº. As an amplification and detection system polymer and labeled by addition of the liquid diaminobenzidine+substratechromogen system and counterstained with Harris hematoxylin. Macroscopically were observed in the liver nodular multifocal areas yellowish, sometimes coalescing, firm, and elevated to the surface that at the cut deepened to the parenchyma. In the left kidney there was a similar tumor mass. In the left frontal lobe, there was nodular focal area, well circumscribed, yellowish and protruding. To cutting surface it compressed the parietal and temporal lobe and showed surface yellowish and smooth. Microscopically, the liver was diffusely infiltrated by mesenchymal neoplasia, expansive, infiltrative, poorly circumscribed and not encapsulated, constituted by spindle cells arranged in interlaced bundles. The cells were elongated with sparse cytoplasm, slightly eosinophilic and indistinct borders with rounded to elongated nuclei, with coarse chromatin and evident nucleoli. In fragments of kidney and brain, neoplastic infiltration similar to that described in the liver was observed. In immunohistochemistry, neoplastic cells were positive with antibodies anti-vimentin and alpha-smooth muscle actin. Discussion: The diagnosis of metastatic leiomyosarcoma in an African goose was based on epidemiological, clinical and pathological findings and confirmed by immunohistochemistry. Reports of neoplasms in birds are relatively rare, however the occurrence of metastatic leiomyosarcoma affecting goose in the most varied locations has been described, from skin to organs of the coelomic cavity like kidney, ovary and intestinal wall. In this case, there is the unusual occurrence of dissemination in the liver, kidney and cerebral cortex, progressing to a neurological clinic condition. There are rare cases of metastatic leiomyosarcoma in geese African goose (Anser cygnoides). The main differential diagnoses include fibrosarcomas, neurofibrosarcomas and histiocytic sarcomas, which are similar macroscopically and histologically. Keywords: ornithopathology, mesenchymal neoplasms, anseriformes. Descritores: ornitopatologia, neoplasias mesenquimais, anseriformes. Título: Leiomiossarcoma metastáticoem ganso africano (Anser cygnoides)